Polska droga do euro - Balcerowicz, Leszek (The Polish way to euro, 2006)
It is easier to say what the Polish way to euro should be than what it will be in fact. The author analyses the first problem and tries to answer the question how joining the eurozone will influence to the economic growth in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 120-122